Endosperm culture-based allotriploid hybrid production from an interspecific cross of Haemanthus spp.: new insights into polyploidization and hybridization - Arisa Nakano; Masahiro Mii; Yoichiro Hoshino (BMC Plant Biology)
Abstract Background Allopolyploid plants are valuable for plant breeding because they have the advantage of polyploidization and hybridization, such as increased vigor and adaptability. Although biparental triploid endosperms have the potential to be used to produce allotriploid plants, the approach remains largely unexplored. Therefore, this study aimed to produce allotriploid plants from the endosperms of interspecific crosses between Haemanthus pauculifolius and H. albiflos. Results Precisely identified embryo and endosperm pairs were used. Embryos were grown on half-strength Murashige and Skoog (MS) medium, and endosperms from interspecific crossing were cultured to induce callus formation and shoot regeneration, which then developed into plantlets. MS medium supplemented with 4-amino-3,5,6-trichloropicolinic acid (picloram) and 6-benzylaminopurine (BAP), or 2,4-dichloro phenoxy acetic acid (2,4-D) and BAP were used for callus induction, and callus formation rates were measured. Flow cytometry, karyotyping, and Sanger sequencing of the nuclear internal transcribed spacer (ITS) region, chloroplast (trnL-trnF region, matK gene), and mitochondrial (nad1 gene) DNA were performed on plantlets derived from embryos and endosperms, along with their parental plants. In this study, a total of 18 pairs of diploid and triploid plantlets were obtained from the embryo and endosperm, respectively. Callus formation rates were significantly higher on media with picloram and BAP compared to 2,4-D and BAP. ITS sequencing and karyotype analyses detected that all the 16 pairs of plantlets analyzed were hybrids, indicating that most endosperm-derived plantlets were allotriploid with a parental chromosome ratio of 2:1 (maternal: paternal). In addition, chloroplast DNA sequencing revealed maternal inheritance in the endosperm-derived plantlets, consistent with embryo-derived plantlets. Conclusions This study is the first to demonstrate the production of allotriploid hybrid plants through endosperm culture using seeds from interspecific crosses, as supported by cellular and genetic analyses. Additionally, the study established a novel system for simultaneously producing diploid and allotriploid hybrids from a single seed, providing valuable materials to study the effects of polyploidization and hybridization in allopolyploid plants. These findings contribute to plant breeding strategies and advance our understanding of hybridization, polyploidization, and allopolyploid plant development.